Advances in the Diagnosis and Management of Age-Related Macular Degeneration - Tahir Ali, Jehan Zeb Khan, Muhammad Waseem, Syed Amir Hamza, Maria Sultan, Salahuddin (Pakistan Journal of Medical & Health Sciences, 2023)
Background: One of the main causes of vision loss in older persons is age-related macular degeneration (AMD), and advances in imaging and therapy have greatly improved the management of this condition. Objective: This study aimed to explore recent advancements in the diagnosis and management of AMD, focusing on emerging technologies, novel therapeutic strategies, and their clinical implications. Methodology: A hospital-based, cross-sectional observational study was conducted from November 2022 to April 2023 at the department of Ophthalmology, Mardan Medical Complex, Mardan and Bacha Khan Medical Complex, Swabi. There were 198 individuals with clinically confirmed AMD who were 50 years of age or older. Comprehensive eye exams, imaging (OCT, FAF, FA), and patient interviews were used to gather data. Using SPSS version 25.0, statistical analysis was carried out to evaluate correlations between AMD severity, risk variables, and treatment results using chi-square and logistic regression tests. Results: Out of the 198 patients, 38.38% had wet AMD and 61.62% had dry AMD. The most often used diagnostic technique was OCT (92.93%). The most common therapy (37.37%) was anti-VEGF injections, which improved vision in 36.84% of wet AMD patients and stabilized 50% of them. The severity of AMD was substantially correlated with age (p = 0.038), smoking (p = 0.012), hypertension (p = 0.026), and diabetes (p = 0.005). Conclusion: Although AMD care has improved because to focused medications and advanced imaging, there are still issues that need for further study into new treatments and long-term patient outcomes. Keywords: Age-related macular degeneration, OCT, anti-VEGF, risk factors, imaging, treatment outcomes.